ELECTRONIC WALLET ADOPTION AND CONSUMER FINANCIAL BEHAVIOR IN DIGITAL PAYMENT SYSTEMS: A LITERATURE STUDY - Husna, Ziadatul; Saputra, Irman; Chaidir, Taufiq (Journal of Finance, Economics and Business, 2025)
The rapid advancement of information technology has accelerated the shift from cash-based transactions toward digital payment systems, placing electronic wallets (e-wallets) at the core of contemporary financial ecosystems. This study aims to synthesise existing literature on digital payment systems, with particular attention to e-wallet adoption and its implications for consumer financial behavior. Using a qualitative literature review approach, this research integrates theoretical perspectives and empirical findings from prior studies in the areas of technology acceptance, digital finance, and consumer behavior. The review indicates that e-wallet adoption is primarily driven by perceived usefulness, perceived ease of use, and trust-related factors, which are especially salient in financial technology contexts. Beyond adoption, the findings reveal that e-wallet usage produces varied behavioral outcomes. While increased payment convenience and reduced transaction friction may encourage impulsive spending, informational features embedded in e-wallet applications can enhance financial awareness and support more disciplined consumption decisions. These contrasting effects suggest that the influence of e-wallet usage on consumer behavior is context-dependent and shaped by application design, user engagement, and situational factors. Overall, this study concludes that e-wallet adoption and post-adoption behavior are interconnected processes that jointly influence individual financial behavior and the broader evolution of digital payment systems. By integrating insights from technology acceptance theories and consumer behavior research, this literature-based study contributes to a more comprehensive understanding of digital payment dynamics and provides a foundation for future empirical research and policy development in the digital finance domain.